2012
DOI: 10.1111/j.1096-3642.2011.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and morphological characterization of Allotettix simoni (Bolívar, 1890) and implications for the systematics of Metrodorinae (Orthoptera: Tetrigidae)

Abstract: Characters used to diagnose the subfamily Metrodorinae (Bolívar, 1887) (Orthoptera: Tetrigidae) are largely variable or homoplastic. Relevant traits used to distinguish amongst subfamilies of Tetrigidae, including sensorial structures, mouth parts, and genitalia are not present in any description of representatives of the subfamily Metrodorinae. The identity of Metrodorinae remains thus at stake. Aiming to fill the current lack of knowledge, a complete anatomical description of adult and last instar nymphs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…All trees showed Trachytetix bufo and Yunnantettix bannaensis did not form one sister group for Cladonotinae. Our results supported the previous finding that Metrodorinae and Cladonotinae were not monophyletic groups ( Yao, 2008 ; Pavon-Gozalo, Manzanilla & Garcia-Paris, 2012 ; Lin et al, 2015 ). As only two species were included in the subfamilies, more samples are needed to uncover these relationships.…”
Section: Resultssupporting
confidence: 93%
“…All trees showed Trachytetix bufo and Yunnantettix bannaensis did not form one sister group for Cladonotinae. Our results supported the previous finding that Metrodorinae and Cladonotinae were not monophyletic groups ( Yao, 2008 ; Pavon-Gozalo, Manzanilla & Garcia-Paris, 2012 ; Lin et al, 2015 ). As only two species were included in the subfamilies, more samples are needed to uncover these relationships.…”
Section: Resultssupporting
confidence: 93%
“…This was the main character used when the subfamily was established by Bolívar (1887), and Günther also adopted it. Today, typically Metrodorinae are mainly characterized by having the median ocellus and the antenna placed below the eyes, a relatively small divergence of the rami of the frontal costa not forming wide scutellum, and a similar length of the first and third segments of the hind tarsus (Pavón-Gonzalo et al 2012). Many species of Metrodorinae also exhibit the posterior angles of the lateral lobes of the pronotum produced outwards, often becoming acutely spinose.…”
Section: Methodsmentioning
confidence: 99%
“…Other Metrodorinae groups (e.g. Malagassy and South American) are not assessed here because it was already shown that Metrodorinae represents a 'garbage can', a polyphyletic group made for easier identification of macropterous Tetrigidae with uncertain placement (Pavón-Gonzalo et al 2012). Metrodorinae are often defined as a group of genera with antennae with 11-16 segments, filiform antennae without widened segments (there are numerous exceptions from this), narrow scutellum (also numerous exceptions exist), lateral pronotal lobes directed sidewards and not having acute spines (also a character with numerous exceptions).…”
Section: Taxonomic Partmentioning
confidence: 99%